2000
DOI: 10.1001/archneur.57.4.540
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of SCA1, SCA2, SCA3/MJD, SCA6, SCA7, and DRPLA CAG Trinucleotide Repeat Expansion in Patients With Hereditary Spinocerebellar Ataxia From Chinese Kindreds

Abstract: The frequency of SCA3/MJD is substantially higher than that of SCA1 and SCA2 in patients with autosomal dominant SCA from Chinese kindreds, who are non-Portuguese. Clinical expressions of the various types of SCAs overlap one another; therefore, for clinical study it is important to make a gene diagnosis and genetic classification for patients with SCA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
112
3
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(124 citation statements)
references
References 20 publications
7
112
3
1
Order By: Relevance
“…This study showed that the subtype frequencies of SCA in Korea is different from those in neighboring populations; in Chinese Han and Japanese, SCA3 is the most common subtype and the prevalence of SCA 2 is less than 10% [4,5]. The predominance of SCA2 and SCA3 is also compatible with previous small studies in Korea [2,3].…”
Section: Discussionsupporting
confidence: 87%
“…This study showed that the subtype frequencies of SCA in Korea is different from those in neighboring populations; in Chinese Han and Japanese, SCA3 is the most common subtype and the prevalence of SCA 2 is less than 10% [4,5]. The predominance of SCA2 and SCA3 is also compatible with previous small studies in Korea [2,3].…”
Section: Discussionsupporting
confidence: 87%
“…Compared with the averaged frequency of ADCA subtypes in other districts of Japan (Table 1) (Takano et al 1998;Sasaki et al 2003), the low frequency of SCA3/MJD is characteristic of Nagano. SCA3/MJD is the most prevalent ADCA subtype in Japan (Table 1) as well as in the majority of countries (Jardim et al 2001;Tang et al 2000;Stevanin et al 1997;van de Warrenburg et al 2002;Silveira et al 1998;Soong et al 2001). This is also the case in the Niigata (43%) and Nagoya (39%) districts, which are geographically adjacent to Nagano; therefore, the low frequency of SCA3/MJD in Nagano (3%) is noteworthy.…”
Section: Discussionmentioning
confidence: 93%
“…Several studies have indicated that SCA6, SCA3/MJD, and DRPLA are the most prevalent subtypes of ADCA in Japan despite a considerable variation in the frequency of each subtype among districts . The frequency of ADCA subtypes also varies among countries (Jardim et al 2001;Tang et al 2000;Stevanin et al 1997;van de Warrenburg et al 2002;Silveira et al 1998;Soong et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Several geographically localised studies have been conducted on the prevalence of ADCAs, with the focus on the six SCA diseases. With regards to SCA3, the prevalence is at its highest in Brazil (69% of SCA cases), Portugal (58%) and China (49%) and relatively low in USA (21%), India (3%) and Italy (1%) [77,[79][80][81][82][83]. An interesting case is the founder effect of SCA7 in South Africa, where this disease represents 26.6% of SCA diseases [84], a figure that is significantly higher than the 2% occurrence worldwide [78].…”
Section: Prevalence and Incidencementioning
confidence: 99%
“…SCA3 is the most common of the SCA disorders, and is at its highest prevalence in the Azores Islands, Portugal (~1:3472) [134]. SCA3 is widely known to be the most common of the SCA diseases, however, this does fluctuate between populations [67,69,80,84,85,135].…”
Section: Sca3mentioning
confidence: 99%